ANALISIS SPASIAL DAN TEMPORAL PERUBAHAN LUAS RUANG TERBUKA HIJAU DI KOTA BANDUNG - Primaristianti Putri; Alinda FM Zain (http://arl.faperta.ipb.ac.id/, 2010)
Urban development is a process of land use/cover changes, while in the process, it often sacrifices its ecological value in term tobe exchanged into more economic land use. The development in urban infrastructures in the shape of buildings and pavement are concrete examples for a developing city. Urban green space as a part of an urban scape has an important role to maintain the urban ecological quality. But the needs for an urban development often sacrifices the existence of urban green space and may cause an environment degradation.Bandung as the capital city of West Java is one of the major cities in Indonesia. The vast economic growth leads it into the threat of losing its fame for being known as The Flower City. Like other big cities around the world, urbanization in Bandung comes with the enviroment degradation. Based on spatial and temporal analysis on Landsat TM images, urbanization leads to the decreasing urban green spaces. On 2001 urbanization has increased the built area into 62% covers of the whole city area from 46% on 1991.The analysis also shows that there are three major urban green space distributions affected by the land topograpjy. Rice field which dominate flat terrains of the city and low built-up density on the east and south sides of the city, cropland which dominate the hilly parts of the city on the north sides, and non-agricultural green space which dominate parts of the city with high built-updensity. Urbanization in Bandung in 2001 left only about 38%of its green space and is about to decrease more in years to come. The main concern is to preserve the green space in north part of Bandung as the water catchment area, and to preserve the ecological quality of the city by balanced the vast growing buildings with the existence of trees and plants for the sake of the city sustainability.